1978
DOI: 10.1093/infdis/138.4.445
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Etiology of Nongonococcal Urethritis

Abstract: The observation of more than four polymorphonuclear cells (PMN) per high-power field (hpf) in gram-stained smears of urethral secretions was found to differentiate patients with urethritis from patients without urethritis. A urethral discharge was present in 78% of patients with nongonococcal urethritis (NGU). Dysuria without demonstrable urethral discharge and with fewer than four PMN/hpf did not appear to fit into the NGU spectrum. NGU is now defined to include men who have negative urethral cultures for Nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(37 citation statements)
references
References 25 publications
3
34
0
Order By: Relevance
“…Cervicitis was defined as more PMNL than epithelial cells in wet smear. Urethritis is generally defined as .4 PMNL per high power field (HPF) in more than four HPF, 18 but in the current study smears with 5-10 PMNL per HPF were defined as ''grey zone urethritis'' and .10 PMNL per HPF as urethritis. 15 Endocervical specimens were obtained, using three sterile aluminium shafted Rayon swabs (Copan, Brescia, Italy).…”
Section: Patientsmentioning
confidence: 91%
See 1 more Smart Citation
“…Cervicitis was defined as more PMNL than epithelial cells in wet smear. Urethritis is generally defined as .4 PMNL per high power field (HPF) in more than four HPF, 18 but in the current study smears with 5-10 PMNL per HPF were defined as ''grey zone urethritis'' and .10 PMNL per HPF as urethritis. 15 Endocervical specimens were obtained, using three sterile aluminium shafted Rayon swabs (Copan, Brescia, Italy).…”
Section: Patientsmentioning
confidence: 91%
“…29 At STD clinics microscopic examinations of methylene blue or Gram stained urethral and endocervical smears as well as examination of vaginal wet smears are routinely performed. The criteria for male urethritis were defined in 1978 18 but no definition of female urethritis or cervicitis has been established. When the cut of for microscopic urethritis was raised to .10 PMNL/HPF, as proposed by Stamm 30 fewer women in the screening group had this sign whereas all women infected with M genitalium having urethritis had .10 PMNL/HPF thus, the specificity of this sign increased.…”
mentioning
confidence: 99%
“…For men without chlamydial infection, suggested etiologies of NGU include trichomoniasis, herpes simplex virus, and genital Mycoplasma/ureaplasmas, including M. genitalium. In the 1970s, several carefully conducted studies clearly demonstrated that C. trachomatis was the most common demonstrable pathogen, accounting for 30%-40% of cases of NGU [19][20][21] in men. However, in a more-recent, large, multicenter study [22], only 15% (range, 4%-35%; in 11 participating centers) of patients with NGU were found to be culture positive for C. trachomatis.…”
Section: Notementioning
confidence: 99%
“…A Gram-stained urethral smear containing 55 PMNL per high-power (61000) microscopic ® eld (averaged over ® ve ® elds with greatest concentration of PMNLs) 9 , and/or . The identi® cation of 510 PMNL per highpower (61000) microscopic ® eld (averaged over ® ve ® elds with greatest concentration of PMNLs) on a Gram-stained preparation from a FPU specimen.…”
Section: Microscopy Availablementioning
confidence: 99%